2010
DOI: 10.1021/la904862e
|View full text |Cite
|
Sign up to set email alerts
|

Order−Disorder Transition of Nonionic Onions under Shear Flow

Abstract: We have investigated the shear-induced ordering of multilamellar vesicles (onions) in a nonionic surfactant (C(12)E(4)) system using a small-angle light scattering (shear-SALS) and a small-angle X-ray scattering (shear-SAXS) technique. In a narrow shear rate-temperature space, the onions form a two-dimensional (2D) hexagonally close-packed structure that shows characteristic hexagonal scattering patterns in both SALS and SAXS. In the dynamic phase diagram, the ordered onion phase is surrounded by disordered on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…% surfactant [16,27,[29][30][31][32][33][34][35][36][37][37][38][39][40][41][42][43], although shear-induced MLVs can be found in all surfactants of the C n E m type studied so far [26,28,33,[44][45][46][47][48][49][50][51][52][53][54][55]. The shear diagram of C 10 E 3 /water (40 wt.…”
Section: Introductionmentioning
confidence: 99%
“…% surfactant [16,27,[29][30][31][32][33][34][35][36][37][37][38][39][40][41][42][43], although shear-induced MLVs can be found in all surfactants of the C n E m type studied so far [26,28,33,[44][45][46][47][48][49][50][51][52][53][54][55]. The shear diagram of C 10 E 3 /water (40 wt.…”
Section: Introductionmentioning
confidence: 99%
“…An example is the stability of multi-lamellar vesicles (MLVs) upon shearing and temperature variations [11,12]. Knowledge about the MLV formation mechanism is important for various applications, which often depend on the viscosity and rely on the vesicle structures.…”
Section: Introductionmentioning
confidence: 99%
“…Shear-induced MLVs can be stable for a long time, but they do not correspond to the thermodynamic equilibrium structure of the lamellar system [15][16][17][18]. Combining different structural techniques such as X-ray, neutron and light scattering, and NMR (all of these rheo tools equipped), make it possible to investigate fluid structures under flow like MLVs [1][2][3] and to determine their characteristic dimensions [10][11][12]18,20,[22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the vesicle radius decreases with the shear rate; it is often approximately proportional to the square root of the inverse rate [2,14]. Sometimes the polydispersity of the MLV size is so low that periodic structures are formed [13,[15][16][17][18]. However, the simple picture of densely packed spheres is misleading since there are no solvent-filled voids in the system; electron microscopy has shown that space is completely filled by the lamellar phase and that the onions have polyhedral shape [19].…”
Section: Introductionmentioning
confidence: 99%